Meaning mindset theory: a transdiagnostic approach to mental health promotion and intervention for children - Armstrong, Laura Lynne; Watt, Emmalyne; Potter, Catherine Laura; Epperson, Brent L. (Frontiers in Psychology, 2025)
A transdiagnostic approach is increasingly recognized as crucial in the prevention or treatment of child internalizing and externalizing mental health concerns. There is substantial overlap and comorbidity among various mental health concerns and the onset of one mental illness elevates the risk of others, underscoring the potential limitations of singular-focused mental health education or treatment. Meaning Mindset Theory (MMT) is a transdiagnostic framework developed and evaluated over the past decade in Canada as a promising new approach. MMT emphasizes agency over thoughts and behaviors, empathy and social competence skills, and meaningful engagement to enhance resilience for both internalizing and externalizing symptoms. The DREAM Program—Developing Resilience through Emotions, Attitudes, and Meaning is a mental health education program grounded in MMT principles. This program has enhanced meaning mindset—agency over thoughts and behaviors, hope for a future that is good, positive self-concept, and openness to learning, new experiences, and feelings—as well as both internalizing and externalizing mental health. To date, the DREAM program, as well as MMT more broadly, has been tested in diverse populations with school-aged children, families, neurodiverse and intellectually gifted young people, homeless men, and Black families, among others. Future research should explore the efficacy of an MMT in therapeutic settings compared to standard treatments, potentially enhancing mental health intervention strategies for Canadian children and families.